Court cultures in the Muslim world seventh to nineteenth centuries - Fuess, Albrecht; Hartung, Jan-Peter (SOAS/Routledge studies on the Middle East, 2010)
Courts and the complex phenomenon of the courtly society have received intensified interest in academic research over the years. This book provides a comparative perspective on the history of courtly culture in Muslim societies from the earliest times to the nineteenth century, and presents a collection of images of courtly life and architecture